ANALISIS VALIDASI TERHADAP PENGEMBANGAN BUKU AJAR DIGITAL DISERTAI NILAI-NILAI ISLAM UNTUK MENINGKATKAN NILAI PROFETIK PADA MATA KULIAH KEWIRAUSAHAAN - Sangidatus Sholiha; Ira Vahlia; Bahtiar Afwan (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
Muhammadiyah Metro University is one of the Islamic campuses in Lampung Province which has the vision of "Center of Professional, Modern and Enlightening Professional Excellence". Therefore, as a UM Metro lecturer, you are required to develop and apply technology-oriented science based on Islamic values that can be useful and applicable in the business and industrial world. This research is a development research, the product produced in this research is the Digital Textbook of Entrepreneurship which is accompanied by Islamic values to increase the prophetic value in entrepreneurship courses. The development of this digital textbook follows the ADDIE model development procedure. Based on research on validation analysis on the development of digital textbooks accompanied by Islamic values to increase the prophetic value in entrepreneurship courses developed using the ADDIE method through validation tests with the assessment sheet instrument, the average score is 88.5% with valid categories based on the value aspect. Islamic, media aspects and material aspects and are suitable for use in learning.Keywords: Research and Development, Digital Textbook, Entrepreneurship